An Analysis of the Level of Students’ Anxiety on Their Writing Skills - Puspita, Anggun Guna (Institut Agama Islam Negeri (IAIN) Kediri, 2023)
Since English has been a foreign language in Indonesia, many achievements are needed in teaching and learning in school. English as subject material in school has four basic language skills, they are reading, writing, speaking, and listening. In learning English as a foreign language, anxiety is a common issue that hinders the student's learning process, including writing skills. The anxiety experienced by students in writing is called writing anxiety. The aim of this qualitative case study is to find out the level of writing anxiety experienced by students in classX-6 at SMAN 1 Prambon and find out teacher's strategies to help students overcome their writing anxiety. The data were collected through the Second Language Writing Anxiety Inventory (SLWAI) questionnaire by Cheng (2004) and interviews were conducted with students of class X-6 and English teachers. The results show that there is a high level of writing anxiety in class X-6 students, with factors such as low self-confidence, lack of topical knowledge, language difficulties, pressure of perfect work, and pressure of limited time. Meanwhile, the teacher has several strategies to help students overcome their writing anxiety, such as memorizing vocabulary sessions at every meeting, giving random questions to help students develop their ideas, providing writing exercises with layouts and pictures to practice their writing skills, giving motivation in every assessment, doing icebreaking and playing games